2006
DOI: 10.1001/archpsyc.63.6.686
|View full text |Cite
|
Sign up to set email alerts
|

Amygdalar Volume and Behavioral Development in Autism

Abstract: Larger right amygdalar volume at 3 and 4 years of age, but not left amygdalar, hippocampal, or total cerebral volume, is associated with a more severe clinical course and worse outcome at age 6 years in children with autism spectrum disorder. These results provide additional evidence that amygdalar development is implicated in the behavioral impairments found in autism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
115
4
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(141 citation statements)
references
References 49 publications
11
115
4
9
Order By: Relevance
“…Munson et al (2006) found that larger right amygdala volume is positively correlated with atypical social development in young children with autism. However, other neuroimaging studies of social perception in autism have suggested that such findings may be related to task-specific characteristics such as the familiarity of the face stimuli (Pierce et al, 2004; see also Hadjikhani et al, 2004).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Munson et al (2006) found that larger right amygdala volume is positively correlated with atypical social development in young children with autism. However, other neuroimaging studies of social perception in autism have suggested that such findings may be related to task-specific characteristics such as the familiarity of the face stimuli (Pierce et al, 2004; see also Hadjikhani et al, 2004).…”
Section: Introductionmentioning
confidence: 89%
“…Findings from anatomical, behavioral, and functional neuroimaging studies in autism have suggested abnormal structure and function of the amygdala (Baron-Cohen et al, 2000;Munson et al, 2006), although there remain many inconsistencies in results and in interpretation. Kemper (1985, 1988) published seminal findings of normal volume but smaller neuron size and increased cell density in the amygdala as well as several other brain regions of autopsied brains of people with autism.…”
Section: Introductionmentioning
confidence: 99%
“…Another study ) used a limited age group of 3-4 year old children and similarly to Schumann et al found increased bilateral amygdala volumes. In a further study using the same subject group as Sparks et al (Munson et al, 2006) increased right amygdala volume was found to be inversely correlated to social and communicative function. These studies suggest that amygdala enlargement may be a direct function of development, similar to atypical growth patterns of grey matter and TBV in autism.…”
Section: Amygdalamentioning
confidence: 64%
“…To date, findings on amygdala structure in autism have been mixed, with studies indicating reduced (Aylward et al, 1999;Pierce et al, 2001;Rojas et al, 2004) and increased (Abell et al, 1999;Howard et al, 2000;Munson et al, 2006;Schumann et al, 2004;Sparks et al, 2002) volumes, as well as nonsignificant differences (Herbert et al, 2003). Of those reporting decreased amygdala size, the first (Aylward et al, 1999) reported reductions in absolute and relative volume after adjusting for TBV, suggesting a disproportionate decrease.…”
Section: Amygdalamentioning
confidence: 99%
“…Autism is a disorder in which the patients often show an unwillingness to have any social interactions [99,101]. Based on the observation on the morphological changes of the amygdala, it was found that there was a significantly decreased volume of the patients with autism [102]. The volume change of the amygdala may be due to decrease in neurogenesis or decreased in pruning of neurons [99,103].…”
Section: Amygdala and Cortex: Non-traditional Neurogenic Regions And mentioning
confidence: 99%